Arts and Humanities Research in the Innovation System: The UK Example - Bakhshi Hasan; Schneider Philippe; Walker Christopher (Cultural Science)
Innovation is the successful exploitation of new ideas. It is about adding value to products and services, to ways of undertaking tasks, and developing policies through the application of ideas that are new in a particular context. The importance of innovation flows from an understanding that the future of advanced economies lies in exploiting knowledge. This application of new ideas is essential in creating and maintaining high-value products and services which are prized within global markets. Policymakers increasingly recognise that their ability to address urgent social issues also rests on a wholesale commitment to innovation. Solutions to social problems such as terrorism, climate change, public health issues and ageing populations will require fresh thinking and the combined use of technological, cultural, social and economic change. The aim of this paper is to investigate the role that arts and humanities research plays in innovation and the challenges faced in making the most of its knowledge. It then goes on to explore the public funding structures that support this research in the UK, and the work of the Arts and Humanities Research Council (AHRC) in particular.